Analysis of Investment Sensitivity in The Construction of The Gelora Bung Tomo Surabaya Circuit - Leo Agus Sulistianto; Budi Witjaksana; Esti Wulandari (International Journal of Social Science and Community Service, 2024)
Provision of Sports Prasarana is an attempt to fulfill the basic rights of the public to obtain services in sports activities, as listed in Law of the Republic of Indonesia Number 11 of 2022 concerning Sports 2022. The growing automotive industry is one important sector that significantly contributes to Indonesian economic growth. Based on the Surabaya City for 2021-2026 calls for the creation of an integrated area, with the Gelora Bung Tomo area serving as an international sports center and integrating with the growth of trade and service functions in Surabaya's surrounding areas. The aim of this study is to measure the amount of investment income and revenue limits in an effort to reduce the risks associated with the investment in the circuit. We carry out flow calculations using the Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), and Payback Period (PP) methods, and then analyze the sensitivity. We reviewed the sensitivity analysis based on several parameters, including commercial rent income and circuit management costs. The development of Tomo's Gelora Circuit is sensitive to a loss of income from the rental of business or commercial premises of 8%, which will affect a decline in profit, resulting in a negative net present value (NPV) and prolonging the rate of return. Additionally, it is sensitive to an increase in management costs by 12%.